ASSESSMENT OF THE ECONOMICAL EFFECTIVENESS OF BACHTYNSKOE DEPOSIT DEVELOPING - KURYLO, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The main economical and geological characteristics of the Bachtynskoe deposite of fluorspar are given. Dimensions and structures of indices of an economical effectiveness are analyzed.